Poetic Justices and the Legalities of Love - Petersson, Sandra (Victoria University of Wellington Law Review, 2000)
This article was presented as a Victoria University of Wellington Centennial Lecture during Law Festival Week in 1999. The article surveys the use of poetry in written judgments. The author suggests that judges most often quote poetry as a rhetorical device, for one of three common purposes: (a) to comment on the parties or facts; (b) to divert from the legal analysis; (c) to introduce the judgment. In addition to these rhetorical purposes, judges also resort to poetry when required to address the topic of love. In assessing whether to recognise a legal tie between parties in a relationship, love is not an express requirement. Lacking a legal definition of love, judges turn to poets.